Implementation of Discovery Learning to Improve Students' Activities and Learning Outcomes in Basic Laws of Chemistry - Anis Fitria; Dian Novita; Arni Wiyati (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to improve the activity and learning outcomes of students using the discovery learning model on the material of basic laws of chemistry. This research was conducted in Class X.2 of SMA Negeri 6 Surabaya in the 2022/2023 academic year. This type of research is class action research which consists of planning, implementation, observation and reflection. The data analysis method in this study uses the percentage formula and the N-Gain formula. Based on the results of data analysis, it is known that student activities have increased from cycle I to cycle III.The activity of students obtained in cycle I was 54.33%, in cycle II it was 65.66%, and in cycle III it reached 82%. Experienced an increase from cycle I to cycle II by 11.33%, from cycle II to cycle III by 16.33%, and from cycle I to cycle III reached 27.66%. The learning outcomes of students also increased from cycle I to cycle III. From the calculation of the N-Gain formula, it was obtained that the increase in student learning outcomes in cycle I was 0.29 with low criteria, in cycle II it was 0.41 with moderate criteria, and in cycle III it reached 0.71 with high criteria. Based on the results of data analysis, it can be concluded that the discovery learning model can significantly improve the activities and learning outcomes of students on the basic laws of chemistry. Thus, the applied discovery learning has a positive impact on the process and learning outcomes of students in each cycle